MENANGGULANGI STRES MENURUT KONSEP AL-QUR’AN - Yusuf, Musfirotun (IAIN Pekalongan, 2009)
Qur’an is God’s saying that is valued as a miracle, revealed to the last prophet through angel Gabriel, told to us handed down from person to person for generations, and valued as worship to God if it is read. It is began by sūrah al-Fātihah and ended by sūrah an-Nās. Allah revealed the Qur’an in order to be life guidance for Muslim community and direction for His creatures. Qur’an is a very effective medicine to eliminate heartsick like stress, and depression, and to improve human morals. There are so many human beings who suffer that sickness, either in low or heavy level. For those who have little faith and piety, they will difficultly overcome it.